Effects of Postharvest Chemical Preservatives on Shelf Life of Tomato (Lycopersicon esculentum cv. Srijana) - Mahesh K. C.; Bronika Thapa; Archana Bhatt; Sabina Aryal; Biraj Poudel (AgroEnvironmental Sustainability)
In recent years, the practice of increasing the shelf life of post-harvest crops is gaining attention worldwide due to the failure of proper techniques to increase post-harvest shelf life. Tomatoes are fragile and have a low shelf life. It fetches low market prices during on-season production and fetches high market prices during off-season production. To address this scenario, research was conducted to study the effect of different preservatives on various physiochemical attributes of tomato (Lycopersicum esculentum). The effects of preservatives were studied on shelf life, disease infestation days, total soluble solids (TSS), titratable acidity (TA), pH, and weight loss percentage (WLP) at 2-day intervals during the storage period. The 7 treatments used were 2% CaCl2, 4%, CaCl2, 1% GA3, 3% GA3, 1000 ppm sodium benzoate, 2000 ppm sodium benzoate, and control in distilled water with 3 replications each. Each replication was immersed in a chemical preservative for 20 minutes and kept in a polyethylene bag. Among the treatments, fruits treated with 3% GA3 recorded the longest shelf life of 31.33 days, followed by 1% GA3 (27 days) and 4% CaCl2 (22 days) over the control (15.667 days). Disease incidence days were highest for 3% GA3 (32.33 days) followed by 1% GA3 (28.33 days) and 4% CaCl2 (23 days) over control (16.667 days). The percentage of physical weight loss on the day of data recording was minimum for 3% GA3 treated fruits and maximum for control. Similarly, TA, TSS, and pH of treated fruits show significant results over control.